The N-linking glycosylation system from Actinobacillus pleuropneumoniae is required for adhesion and has potential use in glycoengineering - Cuccui,J; Terra,VS; Bossé,JT; Naegeli,A; Abouelhadid,S; Li,Y; Lin,CW; Vohra,P; Tucker,AW; Rycroft,AN; Maskell,DJ; Aebi,M; et al. (Open Biology, 2017)
Actinobacillus pleuropneumoniae is a mucosal respiratory pathogen causing contagious porcine pleuropneumonia. Pathogenesis studies have demonstrated a major role for the capsule, exotoxins and outer membrane proteins. Actinobacillus pleuropneumoniae can also glycosylate proteins, using a cytoplasmic N-linked glycosylating enzyme designated NGT, but its transcriptional arrangement and role in virulence remains unknown. We investigated the NGT locus and demonstrated that the putative transcriptional unit consists of rimO, ngt and a glycosyltransferase termed agt. From this information we used the A. pleuropneumoniae glycosylation locus to decorate an acceptor protein, within Escherichia coli, with a hexose polymer that reacted with an anti-dextran antibody. Mass spectrometry analysis of a truncated protein revealed that this operon could add up to 29 repeat units to the appropriate sequon. We demonstrated the importance of NGT in virulence, by creating deletion mutants and testing them in a novel respiratory cell line adhesion model. This study demonstrates the importance of the NGT glycosylation system for pathogenesis and its potential biotechnological application for glycoengineering.